CHARACTERISTICS OF MIDDLE UTERINE ARTERY AND FETAL UMBILICAL BLOOD FLOW IN PREGNANT MURRAH BUFFALO - SINGH, G; CHANDOLIA, R K; DUTT, R; SAINI, A; MALIK, R K (The Indian Journal of Animal Reproduction, 2022)
Six healthy Murrah buffalo were assessed for middle uterine artery and fetal umbilical blood flow at regular interval from day 18 of gestation onward. Resistance index and pulsatility index of middle uterine artery was invariably similar (p>0.05) from day 30 of gestation onward. However, these indices exhibited a decreasing (p<0.05) trend till nine-month of gestation in fetal umbilicus. In brief, the doppler indices of fetal umbilicus suggested the decrease in resistance of blood flow to the fetus.